Elevation of platelet and monocyte activity markers of atherosclerosis in haemodialysis patients compared to peritoneal dialysis patients - Stach-Jablonski, Ksenija; Akın, Ibrahim; Borggrefe, Martin; Krämer, Bernhard; Kälsch, Thorsten; Kälsch, Anna-Isabelle (Mediators of inflammation, 2017)
Purpose. The predominant cause of mortality in dialysis patients are cardiovascular events. Platelet and monocyte activity markers play an important role in cardiovascular mortality and were assessed and related to dialysis quality criteria in haemodialysis (HD) and peritoneal dialysis (PD) patients. Methods. For this prospective comparative study, HD patients () and PD patients () were included. In whole blood samples, surface expression of CD62P and CD40L on platelets, tissue factor binding on monocytes, and platelet-monocyte aggregates were measured by flow cytometry. Plasma levels of MCP-1, IL-6, TNFα, and soluble CD40L were analysed by enzyme-linked immunosorbent assay. Results. Haemodialysis patients showed a significantly higher CD62P expression on platelets (), significantly higher amount of platelet-monocyte aggregates (), and significantly more tissue factor binding on monocytes () compared to PD patients. In PD patients, a significant correlation between Kt/V and platelet CD40L expression (; 0.001) and between Kt/V and platelet CD62P expression (; ) was observed, while there was no significant correlation between Kt/V and tissue factor binding on monocytes and platelet-monocyte aggregates, respectively. Conclusion. Platelet and monocyte activity markers are higher in HD patients in comparison with those in PD patients, possibly suggesting a higher risk of cardiovascular morbidity and mortality.
Gesehen am 08.05.2018